2020
DOI: 10.1101/2020.08.13.249433
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ex vivodetection of SARS-CoV-2-specific CD8+ T cells: rapid induction, prolonged contraction, and formation of functional memory

Abstract: CD8+ T cells are critical for the elimination and long-lasting protection of many viral infections, but their role in the current SARS-CoV-2 pandemic is unclear. Emerging data indicates that SARS-CoV-2-specific CD8+ T cells are detectable in the majority of individuals recovering from SARS-CoV-2 infection. However, optimal virus-specific epitopes, the role of pre-existing heterologous immunity as well as their kinetics and differentiation program during disease control have not been defined in detail. Here, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Presented SARS-CoV-2 peptides are immunogenic Several studies have reported T cell reactivity toward the SARS-CoV-2 HLA-predicted peptides (Grifoni et al, 2020;Nelde et al, 2020;Sekine et al, 2020;Woldemeskel et al, 2020;Zhang et al, 2020). We compiled a map of all the available data of experimentally validated reactive SARS-CoV-2 peptides (Le Bert et al, 2020;Minervina et al, 2020;Nelde et al, 2020;Poran et al, 2020;Schulien et al, 2020;Shomuradova et al, 2020;Snyder et al, 2020;Tarke et al, 2020;Woldemeskel et al, 2020;Wong et al, 2020) and searched it to see if it includes any of our identified peptides (Figure 4). Indeed, seven of our peptides were previously found to be immunogenic in blood samples of COVID-19 patients.…”
Section: Peptide Similarity To Other Coronaviruses and To The Human Proteomementioning
confidence: 99%
“…Presented SARS-CoV-2 peptides are immunogenic Several studies have reported T cell reactivity toward the SARS-CoV-2 HLA-predicted peptides (Grifoni et al, 2020;Nelde et al, 2020;Sekine et al, 2020;Woldemeskel et al, 2020;Zhang et al, 2020). We compiled a map of all the available data of experimentally validated reactive SARS-CoV-2 peptides (Le Bert et al, 2020;Minervina et al, 2020;Nelde et al, 2020;Poran et al, 2020;Schulien et al, 2020;Shomuradova et al, 2020;Snyder et al, 2020;Tarke et al, 2020;Woldemeskel et al, 2020;Wong et al, 2020) and searched it to see if it includes any of our identified peptides (Figure 4). Indeed, seven of our peptides were previously found to be immunogenic in blood samples of COVID-19 patients.…”
Section: Peptide Similarity To Other Coronaviruses and To The Human Proteomementioning
confidence: 99%
“…As was the case for antibodies, reports of virus-specific T cell frequencies have varied between studies based on host group and assay. Both CD8+ and CD4+ T cell cross-reactive populations have been identified, and for each population, cross-reactive peptide epitopes have been described [73][74][75][76][77][78]80,81]. T cells may exhibit a variety of effector functions toward SARS-CoV-2 or common cold HCoVs including the secretion of cytokines/chemokines, the killing of SARS-CoV-2 infected cells (cytotoxic T lymphocyte, CTL), the provision of help by cognate interactions with B cells (T helper [TH] or T follicular helper [TFH]), and/or the targeted down-regulation of an immune response (Regulatory T cell, Treg).…”
Section: T Cells Cross-react With Common Cold Hcovs and Sars-cov-2mentioning
confidence: 99%
“…To determine cellular recruitment efficiency and memory profiles, SARS-CoV-2-specific CD8 + T cell epitopes (peptides + MHC) have been identified using both peptide stimulations and peptide-MHC class I tetramer binding (23)(24)(25)(26)(27)(28)61). Identification of SARS-CoV-2 CD8 + T cell specificities restricted by prevalent human HLAs, including HLA-A * 01:01, HLA-A * 02:01, HLA-A * 03:01, HLA-A * 11:01, HLA-A * 24:02, HLA-B * 07:02, HLA-B * 27:05, HLA-B35:01, HLA-B * 40:01, and HLA-B * 44:03 allowed us to understand the magnitude and phenotype of SARS-CoV-2-specific CD8 + T cells directly ex vivo or after in vitro stimulation.…”
Section: Tracking Recruitment Efficiency Of Sars-cov-2 Epitope-specific Cd8+ T Cell Responses By Tcr Signaturesmentioning
confidence: 99%
“…The characterization of functional antiviral cytokine and activated T cells elicited by SARS-CoV-2 infection by in vitro stimulation has used either HLA optimized peptide "megapools" (18,19), selected expected crossreactive peptides (20), comprehensive peptidome with the omission of ORF1 (21), or whole peptidome functional pools (22). Antigen-specific responses once a peptide epitope has been identified (23) can also be quantified by pMHC binding using tetramers or multimers which is useful for downstream cellular characterization (23)(24)(25)(26)(27)(28). Furthermore, antigen-specific responses have also been identified by mapping of HLA presented peptides during in vitro infection to reveal cryptic T cell epitopes within proteins that are boosted by recent infection in patients with COVID-19 (17), which can be ORF independent, and therefore cryptic epitopes can be generated during infection (19).…”
Section: Introductionmentioning
confidence: 99%